Simple visual parameters for objective assessment of arthroscopic skill. - Alvand, A; Khan, T; Al-Ali, S; Jackson, W; Price, A; Rees, J (2012)
Restrictions placed on the working hours of doctors over the past decade have resulted in substantial changes to the training and assessment of orthopaedic surgical residents. Many who are responsible for training the surgeons of the future have become concerned that this reduced clinical exposure is having a detrimental impact on technical skill acquisition. Consequently, there is a need for surgical educators to develop more objective methods for assessing surgical skill. The primary aim of this study was to determine whether a novel set of visual parameters assessing visuospatial ability, fine motor dexterity, and gaze control could objectively discriminate among various levels of arthroscopic experience. The secondary aim was to evaluate the correlations between these new parameters and previously established technical skill assessment methods.